Surface movement and crack development laws of super-long working faces in medium-depth coal seam mining - Hou, Pengfei; Wang, Shuangming; Feng, Dong; Xie, Xiaoshen; Hou, Enke (Frontiers in Earth Science, 2025)
IntroductionWith the increased application of super-long working faces in coal mining, the surface movement and crack development laws of super-long working faces present an urgent problem to be studied and solved. This study aimed to determine the surface movement and crack development laws of super-long working faces when mining medium-depth buried coal seams.MethodsThe research area in Xiaobaodang No. 2 coal mine, China, was the adjacent working faces 01, 02 and 03, with inclination widths of 300 m and 450 m, respectively. The laws were determined by applying methods such as manual surface movement observation, GNSS automatic surface movement observation, surface crack observation, and crack morphology tracing.ResultsCompared to the working face with an inclination width of 300 m, the maximum subsidence, maximum horizontal movement value, and maximum subsidence coefficient of the super-long working face with an inclination width of 450 m increased by 15.31%, 4.56%, and 16.13%, respectively. Under the influence of mining the 02 working face, the maximum subsidence of the 01 working face increased by 15% and the surface subsidence patterns of the 01 and 02 working face inclination observation lines showed an asymmetric W shape.DiscussionThe widths of the cracks parallel to the open-off cut followed the dynamic development law of opening first, then closing or semi-closing. The widths of the cracks parallel to grooves followed the dynamic development law of opening first, then remaining open. The study results are important to protect mining buildings and the ecological environment.